The role of active surveillance and cytoreductive nephrectomy in metastatic renal cell carcinoma - Amanda Nizam; Jonah A. Schindelheim; Moshe C. Ornstein (Cancer Treatment and Research Communications, 2020)
Treatment of metastatic renal cell carcinoma (mRCC) has been revolutionized by an expanding armamentarium of systemic therapies, which have resulted in improved patient outcomes. Multimodal approaches that include cytoreductive nephrectomy (CN), immunotherapy, and targeted therapy are necessary to optimize clinical care. Active surveillance (AS) and CN are two cornerstones of treatment in mRCC, which require reexamination in the context of new systemic therapies. Herein, we review the data and provide a practical approach for the incorporation of AS and CN in the management of mRCC.